Diane fossey - Gogerly, Liz; Lee, Anna (Hodder Wayland London, 2005)
Telling the story of Fossey's life from her childhood in California to her years as head of a major research project in Rwanda and her violent death, this book looks at the impact of her work on the wider world. It explains the methods behind her insights into the lives of mountain gorillas and the similarities between them and human beings.